Improving Students’ Writing Skill By Using Mind Mapping Technique At The Tenth Grade Of SMK Swasta Kristen BNKP Luzamanu In 2022/2023 - Inka Nofameltriani Harefa; Hidayati Daeli; Elwin Piarawan Zebua; Nursayani Maru’ao (Journal on Education, 2023)
Writing is the important skill that must be master by the students. However, the students had the several problems that caused the Minimum Competence Criterion (MCC) couldn’t achieve by the students they are: the students aren’t able to master the language features, generic structure, and social function of descriptive text; the topic is unfamiliar; the students don’t find interesting and appropriate writing technique; and the students are difficult to generate their ideas. The research aims to improve students’ writing skill in descriptive text by using Mind Mapping Technique at the Tenth Grade of SMK Swasta Kristen BNKP Luzamanu in 2022/2023. The research was conducted by using Classroom Action Research (CAR) and it was applied in two cycles. Each cycle consisted of two meetings and each meeting consisted of planning, acting, observing, and reflecting. Cycle I showed that there were 3 (10,71%) students in excellent category, 3 (10,71%) students in good category, 8 (28,57%) students in average category, 9 (32,14%) students in poor category, and 5 (17,85%) students who classify in very poor category. The result show that most of the students couldn’t pass the MCC. In the Cycle II, it showed that there were 13 students (46,42) who could be classified excellent category and there 15 (53,57) students who could be classified good category. There was no student classified in poor and very poor category”. The average of students’ value was 81. It can be concluded that Mind Mapping Technique improved the students’ writing skill especially in writing descriptive text.